2002
DOI: 10.1097/00005768-200207000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle training fails to improve endurance capacity in athletes

Abstract: These results suggest that IMT significantly improves respiratory muscle strength and endurance. However, these improvements in respiratory muscle function are not transferable to VO2max or endurance exercise capacity as assessed at 85% VO2max in competitive athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 23 publications
12
65
0
3
Order By: Relevance
“…Studies that have specifically trained the respiratory muscles have reported either an improvement (16,17,28,33,78,84,119,124,131) or no change (25,29,38,57,92,117,140) in whole body exercise tolerance. A concern with all of these studies, however, is that endurance performance was evaluated using fixed work-rate tasks sustained to the limit of tolerance.…”
Section: Overcoming the Respiratory Limitations To Exercisementioning
confidence: 99%
“…Studies that have specifically trained the respiratory muscles have reported either an improvement (16,17,28,33,78,84,119,124,131) or no change (25,29,38,57,92,117,140) in whole body exercise tolerance. A concern with all of these studies, however, is that endurance performance was evaluated using fixed work-rate tasks sustained to the limit of tolerance.…”
Section: Overcoming the Respiratory Limitations To Exercisementioning
confidence: 99%
“…However, there is no consensus about an optimal protocol to induce and assess the fatigability of the inspiratory muscles [3]. Although the ergogenic effect of respiratory muscle training (rMT) remains controversial [4][5][6], several recent well-controlled studies have shown that threshold inspiratory muscle training (IMT) [7][8][9][10], as well as voluntary normocapnic hyperpnoea training [10,11] can improve exercise performance in healthy subjects. In general, the functional capacity of the healthy human respiratory system, including the lung, chest wall, and neural control systems, exceeds the demands placed upon it during heavy exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Inspiratory muscle training has been shown to improve performance during cycling and running time trials (km) (10, 20,22,34,38), but has shown mixed results for TTE tests (8,42).…”
Section: Imt and Performancementioning
confidence: 99%
“…We chose to re-examine the concept of IMT effects on hypoxic exercise performance by using a longer fixed distance TT in place of a shorter TTE trial because of the increased reliability (18, 28) and applicability to endurance performance (39). A 20km TT in hypoxia took our subjects approximately 30-40 minutes, compared to the 7-10 minutes that most subjects ran in the TTE trial in Downey et al Additionally, we selected cycling as the mode of exercise versus running, as used in Downey et al, because IMT has been shown to have more consistent, positive effects on cycling performance than running performance (20,34,42).…”
Section: Time Trial Performancementioning
confidence: 99%